Pengaruh Kepemimpinan Transformasional dan Kompensasi Terhadap Kepuasan Kerja dengan Kinerja Pegawai Sebagai Variabel Intervening (PT Cipta Kridatama Site KIM Jambi) - Zinta Putri; Martha Widian Sari; Ai Elis Karlinda (Jurnal Kewirausahaan Cerdas dan Digital, 2026)
This study aims to analyze the effect of transformational leadership and compensation on job satisfaction with employee performance as an intervening variable at PT Cipta Kridatama Site KIM Jambi. This research employed a quantitative approach using a survey method. The population of this study consisted of all employee of PT Cipta Kridatama Site KIM Jambi totaling 862 employees. The sample was determined using the slovin formula with a 10 percent error tolerance, resulting in 90 respondents. The sampling technique used was proportionate stratified random sampling. Data were collected through structural questionnaires and analyzed using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) With The Assistance Of Smartpls 3 Software.  The result of  the study indicate that transformational leadership and compensation have a positive and significant effect on employee performance. Transformational leadership and compensation also have a positive and significant effect on job satisfaction. Furthermore, employee performance has a positive adn significant effect an job satisfaction.  The mediation test result show that employee performance is able to mediate the effect of transformational leadership and compensation on job satisfaction.These findings suggest that improving job satisfaction cannot be achieved solely through leadership and compensation policies, but also requires efforts to enhance employee performance. Therefore, organizations are encouraged to implement effective transformational leadership practices and fair compensation systems to improve employee performance and job satisfaction, particularly in high demand industries such as mining services.